Securitization of Climate Change in Pakistan - Kalim Ullah; Ayesha Imtiaz Abbasi (ASIAN Journal of International Peace & Security (AJIPS), 2024)
In Pakistan, the focus had always remained on traditional means of security. Although Pakistan signed the United Nations Framework Convention on Climate Change at Rio in 1992 and became a member of the two other multilateral agreements in regard to the climate change which were “Kyoto Protocol” of 1997 under UNFCC and “Paris Agreement” of 2016 but the issue of climate change did not receive much attention. This paper explores the securitization of climate change in Pakistan by analyzing how climate-related threats have been transformed from a political to security issue. As described in the “Copenhagen Security Framework”, in international relations and international politics, once the matter is securitized, it gets extraordinary attention. The more attention and discussion an issue receives, the highly securitized the issue gets. By uses qualitative method of study, this paper examines key events and policies, including the 2012 and 2021 National Climate Change Policies formed after devastating floods, the role of international agreements and the integration of climate security into “National Security Policy” of Pakistan.